Characterization of the Role of FruR in Listeria monocytogenes Virulence and Identification of Its Regulons. (March 2022) - Chowdhury, Q.M.M.K.; Ramachandran, R.; Ozdemir, O.; Lawrence, M.L.; Abdelhamed, H.
Abstract : Purpose: Listeria monocytogenes is a Gram-positive intracellular pathogen that cause listeriosis, a fatal foodborne disease for human and animals. Pathogenesis of L. monocytogenes is tightly controlled by transcriptional regulators . Among these regulators, we found the genome of L. monocytogenes F2365 contains seven members of the DeoR-family of regulators. Although some members of the DeoR-family have been studied in several bacteria, its function in L. monocytogenes is unexplored, even though sugar metabolism is crucial for virulence. The goal of the present study was to assess the importance of fruR (LMOF2365_2307), which encodes a DeoR-family transcriptional regulator, in the virulence of L. monocytogenes . Methods & Materials: Overlap extension PCR and allelic exchange were used to construct an L. monocytogenes strain lacking fruR (Δ fruR ). To determine the role in in vivo and intracellular virulence, mice model challenges and plaque assay in murine L2 fibroblast cell lines were conducted, respectively. Furthermore, RNA-seq analysis were performed to identify upregulation and downregulation of genes due to deletion of fruR. Results: In the murine model, deletion of fruR severely decreased virulence compared to parent F2365 strain, and constitutive activation of PrfA, a key virulence regulator of L. monocytogenes, did not restore virulence to Δ fruR strain. Moreover, Δ fruR strain was defective for cell-to-cell spread in L2 fibroblast cells. The Δ fruR strain had an increased lag phase compared to F2365 during growth in media with H2 O2, suggesting that FruR contributes to survival of L. monocytogenes during oxidative stress. Furthermore, RNA-seq analysis revealed that glycolysis and pentose phosphate pathway (PPP) genes were significantly affected by fruR deletion. In particular, FruR induces expression of genes encoding PPP enzymes and suppresses glycolysis genes. Taken together, these results suggest a novel virulence mechanism whereby FruR upregulates the PPP, and this upregulation is necessary for full protection from oxidative stress. Conclusion: This study clarifies the role of FruR in controlling L. monocytogenes carbon metabolism and provides a new mechanism allowing metabolic adaptation of L. monocytogenes to oxidative stress and may assist in the development of intervention strategies to control Listeria infection.